Evaluation of rice bran protein concentrate as soybean meal replacement in practical diets for juvenile black tiger shrimp, Penaeus monodon (Farbricius, 1798) - Huervana, Fredson H. (Miagao, Iloilo University of the Philippines Visayas, 2019)
The potential of rice bran protein concentrate as an alternative protein source to soybean meal in practical diets for juvenile black tiger shrimp. Penaeus monodon, was assessed. Analyses indicate that the rice bran protein concentrate contains 92.3% dry matter, 34.2% protein, 22.8% lipid, 2.2% ash and 2.1% fiber. This feed ingredient was tested in a feeding that designed to replace soybean meal protein in the diets of P. monodon at 0%, 25%, 50%, 75% and 100%. Five isonitrogenous diets were formulated to contain 42% protein. Fifteen juveniles (0.47 + 0.002 g) were randomly assigned in twenty 60-I rectangular tanks equipped with a recirculating seawater system and fed ad libitum for 50 days. Results show no significant differences (P>0.05) among the treatments in terms of weight, % weight gain, daily feed intake, feed conversion ratio (FCR), protein efficiency ratio (PER), specific growth rate (SGR) and survival. Based on the second-order polynomial regression analysis of weight gain, this study suggests that 47.78% rice bran protein replacement level provides the maximum growth for P. monodon. This feed material was found to e highly digestible with apparent dry matter (ADMD) and protein (APD) digestibility coefficients at 83.05 + 0.02% and 87.20 + 0.30%, respectively. Similarly, the apparent digestibility of ingredient (ADI) was high at 85.19 + 0.08% in dry matter and 90.67 + 0.78% in protein. Also the essential amino acids were found to be complete with essential amino acid index (EAAI) of 84 and amino acid chemical score index (ACSI) of 25 with tryptophan as the limiting amino acid. There were no significant differences in whole body composition (dry matter, protein, lipid, ash) of shrimp fed with different levels of rice bran protein replacement. Correspondingly, no significant effects on lipid retention were observed but protein retention exhibited increasing trend with significant increase observed up to 50% replacement level. Collectively the data suggest that rice bran protein concentrate could replace dietary soybean meal protein at 100% without affecting the growth performance and biochemical composition of P. monodon. Rice bran as by product of the rice industry is produced in large quantities in Southeast Asian countries and the utilization of rice bran protein concentrate as feed ingredient is considered a renewable and eco-friendly approach to attaina sustainable production of P. monodon in the ASEAN region.
Thesis (M.S. Fisheries-Aquaculture) - Miagao, Iloilo : CFOS, University of the Philippines Visayas, June 2019